(x-2)(x+4)=x(x+3)-5x

Simple and best practice solution for (x-2)(x+4)=x(x+3)-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-2)(x+4)=x(x+3)-5x equation:


Simplifying
(x + -2)(x + 4) = x(x + 3) + -5x

Reorder the terms:
(-2 + x)(x + 4) = x(x + 3) + -5x

Reorder the terms:
(-2 + x)(4 + x) = x(x + 3) + -5x

Multiply (-2 + x) * (4 + x)
(-2(4 + x) + x(4 + x)) = x(x + 3) + -5x
((4 * -2 + x * -2) + x(4 + x)) = x(x + 3) + -5x
((-8 + -2x) + x(4 + x)) = x(x + 3) + -5x
(-8 + -2x + (4 * x + x * x)) = x(x + 3) + -5x
(-8 + -2x + (4x + x2)) = x(x + 3) + -5x

Combine like terms: -2x + 4x = 2x
(-8 + 2x + x2) = x(x + 3) + -5x

Reorder the terms:
-8 + 2x + x2 = x(3 + x) + -5x
-8 + 2x + x2 = (3 * x + x * x) + -5x
-8 + 2x + x2 = (3x + x2) + -5x

Reorder the terms:
-8 + 2x + x2 = 3x + -5x + x2

Combine like terms: 3x + -5x = -2x
-8 + 2x + x2 = -2x + x2

Add '-1x2' to each side of the equation.
-8 + 2x + x2 + -1x2 = -2x + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
-8 + 2x + 0 = -2x + x2 + -1x2
-8 + 2x = -2x + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
-8 + 2x = -2x + 0
-8 + 2x = -2x

Solving
-8 + 2x = -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-8 + 2x + 2x = -2x + 2x

Combine like terms: 2x + 2x = 4x
-8 + 4x = -2x + 2x

Combine like terms: -2x + 2x = 0
-8 + 4x = 0

Add '8' to each side of the equation.
-8 + 8 + 4x = 0 + 8

Combine like terms: -8 + 8 = 0
0 + 4x = 0 + 8
4x = 0 + 8

Combine like terms: 0 + 8 = 8
4x = 8

Divide each side by '4'.
x = 2

Simplifying
x = 2

See similar equations:

| 180=(2x+2)+(3x+1) | | 3(4x+5)-2(3x-2)=3x+7 | | t*5-4=16 | | 20+3x-2=x^2-4x | | -4b=3(-4b)+7 | | 180=(8x)+x+90 | | 0.86(3.7-2.3x)=4.9 | | (7n-2)(5n-1)=0 | | 0.86(3.7-2.3x)=49 | | 30a^2+7a=0 | | (5v+7)(2+v)=0 | | g(-4b)=3(-4b)+7 | | 2x^3-8x^2-192x=0 | | 6cos+5tan=0 | | 5r+4r-9r= | | 6cisb+5tan=0 | | 2x=-10-2 | | 180=2x+76 | | 180=2x+76+(5x-2) | | 6(3x+5)-5(x-7)=39 | | c=6+5x | | 7x-3=24x+5 | | 7x-3=24x | | 3x+4+4y=16 | | 16=.25b | | b+2.25=5 | | 16=.25 | | 15w*1.25= | | 2(8+6x)+2=4(4+3x)+2x | | 4a^3+12a^2-9a-27=0 | | 45+40a= | | 291.52=8(0.04m+27.70+0.20(27.70)) |

Equations solver categories